Business Management Of Village-Owned Enterprises In Hegarmanah Village: Potential And Islamic Economic Implementation Strategy - Akhmad Nur Zaroni (Universitas 45 Surabaya, 2023)
This descriptive qualitative study design makes use of SWOT and village potential analysis. companies in the real sector—agriculture, cattle, and fisheries—along with trade, tourism, and the agro-industrial sector—were discovered to have the potential to develop into successful village-owned companies in Hegarmanah Village. Although the results of the SWOT analysis point to (a) the SO Strategy Village-owned businesses run their operations using a system for managing business units based on the real sector and business units for Islamic microfinance institutions. Examples of (b) (c) ST strategy, a strategy to create an Islamic economy, include the WO strategy, entrepreneurial strategy, and human resource development. d) The WT Approach Islamic teachings can be applied to increase consciousness, motivate a strong work ethic, and promote syirkah. enticing business participants to engage more, establishing values of care for local products, and developing numerous business lines